2021
DOI: 10.1021/jacs.1c05607
|View full text |Cite
|
Sign up to set email alerts
|

A General Organocatalytic System for Electron Donor–Acceptor Complex Photoactivation and Its Use in Radical Processes

Abstract: We report herein a modular class of organic catalysts that, acting as donors, can readily form photoactive electron donor–acceptor (EDA) complexes with a variety of radical precursors. Excitation with visible light generates open-shell intermediates under mild conditions, including nonstabilized carbon radicals and nitrogen-centered radicals. The modular nature of the commercially available xanthogenate and dithiocarbamate anion organocatalysts offers a versatile EDA complex catalytic platform for developing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(71 citation statements)
references
References 72 publications
2
69
0
Order By: Relevance
“…Further studies revealed that irradiation with visible light facilitated more efficient conversion (entries 4 and 5). We observed that mixing the pyridinium salt 14 , 52 55 with pivalate resulted in a significant shift in the intensity of the UV/Vis absorption peak, suggestive of the formation of a photoactive electron donor–acceptor (EDA) complex (see Supplementary Information for details) 56 63 . Therefore, the intermediacy of the EDA complex further facilitates SET to generate amidyl radicals when irradiated by visible light, thereby promoting the radical chain pathway 49 , 64 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Further studies revealed that irradiation with visible light facilitated more efficient conversion (entries 4 and 5). We observed that mixing the pyridinium salt 14 , 52 55 with pivalate resulted in a significant shift in the intensity of the UV/Vis absorption peak, suggestive of the formation of a photoactive electron donor–acceptor (EDA) complex (see Supplementary Information for details) 56 63 . Therefore, the intermediacy of the EDA complex further facilitates SET to generate amidyl radicals when irradiated by visible light, thereby promoting the radical chain pathway 49 , 64 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above experiment results and previous studies, a plausible reaction pathway for the deaminative cross-coupling of Katritzky salts with silyl enol ethers is depicted in Figure . Initially, silyl enol ethers 1 could interact with Katritzky salts 2 to form the EDA complex A , which could be activated by visible light (427 nm LEDs) irradiation to induce a SET process and deliver the radical ion pair ( B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…By employing this strategy, different electron donors ( D ) have been explored to form the EDA complexes with Katritzky salts, and a series of C–C­(sp 3 ), C–C­(sp 2 ), and C–S bond formation methods has been well developed by the groups of Xu, Melchiorre, and Liao (Figure b). Very recently, Melchiorre and co-workers reported the redox-neutral addition of alkyl radicals to silyl enol ethers via the EDA complex, but organic catalysts were needed as electron donors for the catalytic EDA complex formed (Figure c) …”
Section: Introductionmentioning
confidence: 99%
“…Xanthate and dithiocarbamate salts were successfully employed by Melchiorre as catalysts to promote various photoinduced radical cascade processes. 35 For example, the treatment of vinyl sulfone 41 and N-acyloxy phthalimide 42 with a catalytic amount of xanthate 43 in the presence of γ-terpinene ( 44 ) as a stoichiometric reductant under irradiation with blue LED light afforded hydroalkylation product 45 in good yield ( Scheme 7 ). This Giese-type radical hydroalkylation of vinyl sulfone 41 is initiated by the radical fragmentation of N-acyloxy phthalimide 42 through the photoinduced SET of the EDA complex 46 , providing alkyl radical 47 and thiyl radical 48 .…”
Section: Photoinduced Molecular Transformation Via Sulfur Anion Eda Catalysismentioning
confidence: 99%